The influence of acute dietary nitrate supplementation on performance during a soccer specific treadmill protocol - Peters, G.; Henderson, K.; Stone, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Research shows that dietary nitrate supplementation (DNS), reduces the O2 cost of walking and running (Lansley et al. 2011) Further research suggests that DNS reduced the O2 cost of low intensity exercise, and enhanced tolerance to high intensity exercise (Bailey et al. 2009). Field based research has shown that DNS improves intermittent running performance by around 3.8% when time to fatigue is assessed (Wylie et al. 2013). However no studies so far have examined the effect of acute DNS on the physiological responses to high intensity interval exercise (HIIE). Therefore the aim of the study is to show the effects of DNS on high intensity intermittent running. Methods Participants visited the Human Performance Laboratory (HPL) four times. The first visit was a maximal oxygen uptake (VO2max) test, to volitional fatigue. Following a pilot session, the participants then performed two exercise tests 10 days apart, in a doubly blind randomised crossover design. Participants ingested a 70 ml shot of Beetroot juice (BRJ) containing 0.4 g (4mmol) of dietary nitrate, or 70ml placebo (PL) 60 min prior to an intermittent treadmill protocol. Results At time of submission, seven participants completed study. Mean Oxygen uptake (VO2) was 36.6 and 36.2 ml.kg/min between BRJ and PL respectively. Mean blood lactate concentrations are 4.89 and 5.76 mmol/L for BRJ and PL respectively. Mean blood glucose concentrations are 4.38 and 4.46 mmol/L for BRJ and PL respectively. Perceptual responses are 13 v 12 for BRJ and Pl respectively. Discussion Early results suggest that acute dietary nitrate supplementation reduces the perceptual effort of high intensity exercise, despite no changes in oxygen consumption. Blood lactate and glucose also show no differences between BRJ and PL respectively. Further data to be collected to ensure type I or II errors are not made.